Cellulose-Based Superabsorbent Hydrogels - Mondal, Md. Ibrahim H. (Polymers and Polymeric Composites: A Reference Series,, 2019)
With the prospect of revolutionizing specific technologies, this book highlights the most exciting and impactful current research in the fields of cellulose-based superabsorbent hydrogels with their smart applications. The book assembles the newest synthetic routes, characterization methods, and applications in the emergent area. Leading experts in the field have contributed chapters representative of their most recent research results, shedding light on the enormous potential of this field and thoroughly presenting cellulose-based hydrogel functioning materials. The book is intended for the polymer chemists, academic and industrial scientists and engineers, pharmaceutical and biomedical scientists and agricultural engineers engaged in research and development on absorbency, absorbent products and superabsorbent hydrogels. It can also be supportive for undergraduate and graduate students.